2015
DOI: 10.1519/jsc.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Repeated Isometric Neck Strength and Endurance Testing in a Simulated Contact Posture

Abstract: The purpose of this study was to examine the reliability of repeated isometric measurements of neck strength and endurance in a simulated rugby contact posture. Data were collected from healthy active university students (n = 20) over 3 sessions. Each session consisted of a single maximal voluntary contraction (MVC) and endurance trial for extension and flexion. The endurance trials were analyzed to determine the area under the force curve (%AUC) and the time to fatigue (TTF). Reliability was calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Our results suggest that the extensor muscles may have a larger role to play than previously thought in attenuating forces of impact. The cervical extensors are consistently reported to be the muscle group that generate the highest isometric neck force 25 39 40. It may be possible, therefore, that this strength range represents the greatest defensive mechanism at reducing the force of impacts during sagittal plane impact, previously identified as the most common direction of concussive impacts in male professional rugby players 12…”
Section: Discussionmentioning
confidence: 98%
“…Our results suggest that the extensor muscles may have a larger role to play than previously thought in attenuating forces of impact. The cervical extensors are consistently reported to be the muscle group that generate the highest isometric neck force 25 39 40. It may be possible, therefore, that this strength range represents the greatest defensive mechanism at reducing the force of impacts during sagittal plane impact, previously identified as the most common direction of concussive impacts in male professional rugby players 12…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies investigating neck strength have conducted testing in a seated position with the torso restrained, [33, 34]. Trunk stabilisation is reported, [13] to be essential for reliable and valid neck strength measurements, [34], however trunk stabilisation limits construct validity and the functional relevance of the strength measures, [13]. In this study the trunk was stabilised through the retraction of the scapulae and the horizontal body position with the elbow extended perpendicular to the shoulders and 90° hip and knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the trunk was stabilised through the retraction of the scapulae and the horizontal body position with the elbow extended perpendicular to the shoulders and 90° hip and knee flexion. A previous study,[13] used a similar body position, but with the trunk supported on a bench. The absolute values reported for the control group (Table 3) in the current study were 23 – 83 N stronger than those reported in a similar population,[19] but regardless of the strength differences the patterns reported for each movement direction were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid ballistic movements, participants were asked to first take the strain, and then over a 2-3 second period gradually increase the force to maximal exertion to be held for 3 seconds. Verbal encouragement was provided for each MVC (3 trials in each of the 4 head positions) and a 60-second rest period was given between each trial (Salmon, Handcock, Sullivan, Rehrer, & Niven, 2015). The peak force (kg) was recorded during the 3-second MVC.…”
Section: Strength Testingmentioning
confidence: 99%